The Effect Of Know - Want To Know – Learn Method In Reading Skills Of Grade X At Sma Swasta Al Washliyah 2 Serbelawan - Rohdearni Wati Sipayung; Semaria Eva Elita Girsang; Nanda Nadila Damanik (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
The aim of this research is to find out the significant effect of using KWL Method in reading skills of grade X of SMA Swasta Al Washliyah 2 Serbelawan. This research used quantitative method approach. Population of this research was grade X with one class which consists of 23 students. The technique of collecting data was pre-test and post-test. The technique analysis data by using formula. The result of this research was obtained tcount=10,86 > ttable= 1,717 at the significance level ɑ=0.05 and degrees of freedom (df)= 22, Ho is rejected and Ha is accepted and implies that the students taught by using KWL Method achieve a better score. It means that there is significant effect of using KWL Method in Reading Skills of Grade X at SMA Swasta Al Washliyah 2 Serbelawan. Because the using KWL Method as a method for learning English to reading ability. KWL Method a variety of features, including a dictation function, which makes it easier for students to learn and understand English as reading skills. The students should from a habit of reading by using KWL method to improve their reading skills